Analysis of the Effect of Service Quality on Customer Loyalty in Mediation by Customer Satisfaction at Loka Supermarket Cibubur - I Made Adnyana; Yulianah; Agustiya Hutri Primasari (International Journal of Science and Society, 2020)
The purpose of this research is to study the influence of service quality on customer satisfaction and its impact on customer loyalty at Loka Supermarket Cibubur and to provide suggestions on how Loka Supermarket can increase customer loyalty by increasing the aspects that influence it. The research approach is quantitative research in accordance with data collection in the form of distributing questionnaires to 150 respondents. The results of this study indicate that each of the quality dimensions directly has a positive and significant effect on customer satisfaction at Loka Supermarket Cibubur. Customer satisfaction directly has a positive and significant effect on customer loyalty. And and each dimension of service quality indirectly affects customer loyalty through customer satisfaction.